Characterization of a temporary pond of the north of Colombia and biological and ecological aspects of Dendrocephalus affinis - Serna-Macías, Daniel José (2019)
The aim of this work was to evaluate the water system and the sediments of a temporary pond, in addition to describe the life cycle and asses sex proportions of D. affinis in laboratory conditions. The pond was sampled during the years 2010 - 2012, the physicochemical of the water, granulometry and heavy metals of the sediment were also evaluated. Simultaneously, we took samples of the sediment to collect the cysts that were used to describe the life cycle, survival and sex proportions at laboratory. During the rainy season, the pond showed mesotrophic conditions and in the dry season high organic load. The muddy soil was dominant and allowed the water retention. The heavy metals values were found in the normal ranges of similar systems. The macroinvertebrates associated to the pond were formed by seven orders and 28 genera, which Hemiptera and Coleoptera orders were the most abundant with 39.7 and 31.8 % respectively. Laboratory essays showed that nauplus of D. affinis lived 30 days and had a survival of 31.6%. This work also contributed with a description of a temporary pond and of the life cycle of D. affinis in laboratory conditions. Dendrocephalus affinis showed be organisms with short life cycle, fast grown and high survival ratio, this favor its use as live food potential in the aquaculture.